Phase transformation sequence of pre-oxidized roast-leach ferrovanadium residue - M. Nevondo; L. Koech; O.O. Ola-omole; M.M. Ramakokovhu; M.L. Teffo; R. Sadiku (Heliyon, 2024)
The depletion of the primary metal sources has prompted the exploration of alternative avenues for metal recovery. In the case of titanium and iron, the ferrovanadium residue produced through roast-leach processing of titanomagnetite presents a viable option for accessing these metals. Titanomagnetite resources, which contain valuable elements, such as iron, vanadium, and titanium, possess significant valuable potential. Titanomagnetite deposits are normally treated via smelting for vanadium or vanadium and iron recovery; titanium is not commercially recoverable. Titanomagnetites have recently been processed through the roast-leach method for vanadium primary production, and iron and titanium are typically part of the waste stream in this process. This study proposes a novel approach to determine the characteristic mineralogy and to study the phase transformation sequence of the roasted-leached ferrovanadium residue during the pre-oxidation process. Leaching was also done to evaluate the extraction potential of Fe, V and Ti on the pre-oxidized residue in comparison to the raw residue The roasted-leached ferrovanadium residue was sampled using the cone and quartering method and then, dried in an oven at temperatures of between 30 and 40 °C, for an hour after which, the remaining moisture content was determined. The bond milling method was employed to reduce the sample size, while the particle size distribution (PSD) was verified by using the standard laboratory Tyler series. Thereafter, the roasted-leached ferrovanadium residue was characterized with XRD, SEM, ICP-OES, and XRF. The samples were pre-oxidized at temperatures ranging from 300 °C to 1000 °C with an aim of improving the grades of iron, vanadium, and titanium-bearing minerals prior leaching. The results revealed the moisture content to be ∼5.07%. The bond work index of typical slags was estimated to be 10.2 kwh/t, with a determined d80 value of 200 μm. According to the XRF analysis, the predominant compounds present are hematite, Fe2O3 (75.55%), titanium dioxide, TiO₂ (12.79%), silicon dioxide, SiO2 (3.03%), and alumina, Aℓ2O3 (2.62%), along with minor compounds. XRD patterns exhibited the presence of FeTiO3 and VO2 in the as-received samples, while pre-oxidation induced the evolution of new phases such as hematite, rutile, anatase, and pseudobrookite.